Submission from the CGIAR System Organization, the World Business Council for Sustainable Development (WBCSD), the French National Institute for Agricultural Research (INRA) and the World Bank, in response to Decision 4/CP.23. - CGIAR System Organization; World Business Council for Sustainable Development; Institut National de la Recherche Agronomique, France; World Bank; CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
This submission on Improved nutrient use and manure management towards sustainable and resilient agricultural systems proposes a set of priority action areas for consideration by the Koronivia Joint Work on Agriculture to further the agenda.